Cervical foraminal stenosis causing unilateral diaphragmatic paralysis without neurologic manifestation: A case report and review of the literature. Issue 37 (11th September 2020) - Park, Hyung-Youl; Kim, Ki-Won; Ryu, Ji-Hyun; Lim, Chang-Rack; Han, Sung-Bin; Lee, Jun-Seok
Abstract: Rationale: Unilateral diaphragmatic paralysis due to cervical spondylosis has rarely been reported. We present the first case of unilateral diaphragmatic paralysis without radicular pain or motor weakness due to cervical foraminal stenosis and a review of the related literature. Patient concerns: A 59-year-old man presented with dyspnea and fever. His chest radiograph revealed right hemidiaphragmatic paralysis. Diagnoses: The differential diagnosis of phrenic nerve palsy excluded mediastinal and neurodegenerative diseases. Imaging studies showed right foraminal stenosis caused by cervical spondylosis at C3–4 and C4–5. Interventions: The patient underwent foraminotomy at C3–4 and C4–5 on the right side. The operative findings revealed a severe compression of the C4 root. Outcomes: At 3 months postoperatively, the unilateral diaphragmatic paralysis and dyspnea were recovered. Lessons: Hemidiaphragmatic paralysis deserves careful evaluation for the presence of cervical spondylosis, even without concomitant neurologic manifestations.